2020
DOI: 10.1111/bjh.16327
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of eltrombopag plus pulsed dexamethasone as first‐line therapy for immune thrombocytopenia

Abstract: Summary Current first‐line treatments for immune thrombocytopenia (ITP) usually have transient effects and sustained platelet response off therapy remains low. We evaluated whether eltrombopag plus pulsed dexamethasone as first‐line therapy can increase the proportion of patients maintaining platelet counts >50 × 109/l for a prolonged period without further ITP therapy. Treatment consisted of eltrombopag 25–75 mg daily according to platelet response for 12 weeks plus dexamethasone, 40 mg daily for four consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 36 publications
0
39
0
1
Order By: Relevance
“…Initial response was achieved in 100% of patients at day 33, and SR was kept in 75% of patients at 6 months and 66.7% at 12 months. The promising results of this combination strategy as first‐line therapy for treatment‐naïve ITP were further validated in another single‐arm, pilot study, which reported a SR rate of 56.5% at 6 months 22 . However, the efficacy of corticosteroids plus TPO‐RAs as a frontline treatment for ITP has not yet been evaluated in a prospective, randomized trial.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Initial response was achieved in 100% of patients at day 33, and SR was kept in 75% of patients at 6 months and 66.7% at 12 months. The promising results of this combination strategy as first‐line therapy for treatment‐naïve ITP were further validated in another single‐arm, pilot study, which reported a SR rate of 56.5% at 6 months 22 . However, the efficacy of corticosteroids plus TPO‐RAs as a frontline treatment for ITP has not yet been evaluated in a prospective, randomized trial.…”
Section: Introductionmentioning
confidence: 97%
“…The promising results of this combination strategy as first-line therapy for treatment-naïve ITP were further validated in another singlearm, pilot study, which reported a SR rate of 56.5% at 6 months. 22 However, the efficacy of corticosteroids plus TPO-RAs as a frontline treatment for ITP has not yet been evaluated in a prospective, randomized trial. Here, we reported the results of a prospective, multicenter, randomized, controlled, open-label, phase three clinical trial, in which we compared the efficacy and safety of HD-DXM plus rhTPO vs HD-DXM alone in newly diagnosed, treatment-naïve adult ITP patients.…”
Section: Introductionmentioning
confidence: 99%
“…As a combination for intensified first-line therapy, a single-arm study with dexamethasone followed by a 28-day course of eltrombopag in treatment-naïve subjects showed 83% of patients had an early response and 50% of patients had a complete response at six months [29]. Simultaneous combination of eltrombopag and high-dose dexamethasone therapy could generate a sustained, complete, long-term response in adult patients and be used as a viable first-line treatment [30]. TPO-RAs are not universally considered curative, although in one study, 30% of adult patients with ITP maintained platelet counts >50 × 10 9 /L after discontinuation of romiplostim [31].…”
Section: Can We Improve Management?mentioning
confidence: 99%
“…Childhood immune thrombocytopenia is an acquired autoimmune disease characterized by a decrease in platelet count (<100×10 9 /L) and an increased risk of bleeding. 1,2 This thrombocytopenia may be due to reduced platelet production and immune-mediated destruction, but usually involves glycoprotein autoantibodies expressed on megakaryocytes. [3][4][5] ITP is the most common hemorrhagic disease in children, accounting for one-third of hemorrhagic diseases, 6 Its onset is usually acute and short-lived, with an incidence of approximately (2~5)/10 million.…”
Section: Introductionmentioning
confidence: 99%